Liquid Level Control System Using Arduino and Matlab-GUI - Risfendra Risfendra; Miftahul Jannah; Dwi Sudarno Putra (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2022)
Control of the liquid level in the industry is very concerning. Without liquid level control, the output of the liquid level will be different, this will result in a different output that affects the process. However, for monitoring the level and filling of the resulting storage tank, for example, the procedure remains conventional, it's miles essential to reveal the machine in order that paintings may be finished correctly and effectively. This examine proposes tracking the liquid stage machine the usage of Arduino Uno primarily based totally on Matlab Graphical User Interface (GUI). The parameters monitored are the given setpoint and the measured liquid stage withinside the tank. The prototype for tracking the liquid stage machine became made on this examine to be examined at the machine. The effects of the checks finished display that the proposed liquid stage tracking machine has been capable of well reveal stage parameters. Kendali atau kontrol terhadap level cairan pada industri termasuk salah satu yang sangat diperhatikan. Tanpa kontrol level cairan, keluaran level cairan akan berbeda, hal ini akan menghasilkan keluaran yang beda sehingga mempengaruhi proses. Namun, untuk pemantauan level dan pengisian tangki penyimpanan yang dihasilkan, misalnya, prosedurnya tetap konvensional, maka perlu dilakukan monitoring sistem agar pekerjaan dapat dilakukan dengan baik dan tepat guna. Penelitian ini mengusulkan sistem monitoring level cairan menggunakan Arduino Uno berbasis Graphical User Interface (GUI) Matlab. Parameter yang dimonitor adalah setpoint yang diberikan dan level cairan dalam tangki yang terukur. Prototype sistem monitoring level cairan dibuat dalam penelitian ini untuk diujicobakan pada sistemnya. Hasil pengujian yang dilakukan menunjukan bahwa sistem monitoring level cairan yang diusulkan telah mampu memonitor parameter level dengan baik.